A brief review on circular economy pathways in plastic recycling - Abd Razak, Jeefferie; Azraai, Shamsul Bahari; Semiun, Nasri; Narayanan, Thinakaran (Research and Scientific Innovation Society, 2026)
Plastic waste has become one of the defining sustainability challenges of our time, demanding a decisive shift from the linear “take–make–dispose” model toward a circular plastic economy. This brief review paper examines how circularity in plastics is being advanced through innovative approaches such as product redesign, advanced recycling technologies, and policy instruments, including Circular Economy Blueprints and Extended Producer Responsibility (EPR). Yet, the transition is constrained by systemic barriers: deficits in infrastructure, uneven public awareness, weak enforcement, and fragmented regional strategies. Beyond technical interventions, the circular economy of plastics requires a social perspective that acknowledges the environmental, economic, and societal costs of mismanaged waste. Failures in recycling systems intensify hidden risks, notably microplastic pollution and human health impacts, underscoring the urgency of comprehensive reform. Pathways to overcoming these barriers include strategic regional collaboration, scientific innovation, and inclusive governance frameworks that integrate social responsibility with technological progress. By situating these dynamics within broader debates on sustainable development, this paper offers insights into practical strategies for embedding circularity in plastic recycling and advancing resilience across diverse contexts.